Environmental policy in Malaysia: biomedical waste, strategies and issues / Abdul Raufu Ambali, Ahmad Naqiyuddin Bakar and Farah Murni Merican - Ambali, Abdul Raufu; Bakar, Ahmad Naqiyuddin; Merican, Farah Murni (Faculty of Administrative Science and Policy Studies, 2013)
Management of waste is a general acute problem around the globe. Waste management is of great concern as urbanization and economic development increase leading to generation of larger quantity of waste materials. The management of waste materials requires immediate attention of the newly emerging economy country such as Malaysia. To be more specific, biomedical wastes are becoming a topic of one cannot deny the important roles play by biomedical science and its activities on human life and fitness. However, these activities can generate some wastes that pose severe effects on human health and environment at large, especially if there is no proper management policy in place. Although some may argue that waste is generally unavoidable by-product of most human activities but the provision of expanded healthcare facilities today have added substantial quantities of biomedical waste into waste stream with severe environmental and human health consequences. This paper examines the level of biomedical waste in Malaysia. It also addresses the impacts of these biomedical wastes and the strategic measures taken by Malaysian government. Finally, it identifies some potential issues associated with policy measures and put forward some policy recommendations for precautionary measures in the future.